2014
DOI: 10.1111/nph.12869
|View full text |Cite
|
Sign up to set email alerts
|

Stay‐green alleles individually enhance grain yield in sorghum under drought by modifying canopy development and water uptake patterns

Abstract: SummaryStay-green is an integrated drought adaptation trait characterized by a distinct green leaf phenotype during grain filling under terminal drought. We used sorghum (Sorghum bicolor), a repository of drought adaptation mechanisms, to elucidate the physiological and genetic mechanisms underpinning stay-green.Near-isogenic sorghum lines (cv RTx7000) were characterized in a series of field and managed-environment trials (seven experiments and 14 environments) to determine the influence of four individual sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
209
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(220 citation statements)
references
References 70 publications
10
209
1
Order By: Relevance
“…In crop plants species, stay-green enables a plant to maintain greenness and continue photosynthesising even under stress (Borrell et al 2014). Staygreen is associated with antioxidant status and photosystem II of the mesophyll cells (De Simone et al 2014;Luo et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In crop plants species, stay-green enables a plant to maintain greenness and continue photosynthesising even under stress (Borrell et al 2014). Staygreen is associated with antioxidant status and photosystem II of the mesophyll cells (De Simone et al 2014;Luo et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll content (SPAD value) was used for assessment of staygreen in sorghum, and four stay-green QTL were identified (Harris et al 2007). It was reported that individual alleles for stay-green enhanced grain yield in sorghum under drought by modifying canopy development and water uptake patterns (Borrell et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The reduced leaf area of low tillering varieties would conserve soil moisture for the grain-filling stage in drought-prone regions (Islam and Sedgley, 1981;Kebrom and Richards, 2013). Reduced tillering associated with stay-green drought tolerance loci is also important for grain sorghum production in water-limited environments (Borrell et al, 2014). A more complete understanding of the genetic and biochemical basis of tiller production in sorghum will accelerate progress toward optimal crop canopy architectures and higher yield.…”
mentioning
confidence: 99%
“…Moreover, superior morphological, physiological and biochemical traits were also selected for evaluating drought tolerance of crops (Chen et al, 2012). For example, sorghum with stay-green trait expressed drought tolerance under drought conditions (Borrell et al, 2014). It was noted that these traits could eventually contribute to final yield particularly under drought conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although sorghum is considered as a drought-tolerant crop (Shan, Xu, 2009), its production often suffers from drought in those regions. Sorghum breeders seek to utilize drought tolerant germplasm to mitigate drought stress risk to sorghum production (Borrell et al, 2014). During the sorghum breeding process, it is crucial to improve the screening efficiency and identifying accuracy.…”
Section: Introductionmentioning
confidence: 99%